High and steady or low and rising? : Vocational versus general education in life-cycle earnings - Cörvers, Frank [Verfasser]; Heijke, Hans [Verfasser]; Kriechel, Ben [Verfasser]; Pfeifer, Harald [Verfasser] (My University, 2010)
"In this paper, we compare experience-earnings profiles of employees with vocational and general education background in Germany, the Netherlands and the United Kingdom, three countries with fundamentally different education systems. Using Mixed-Effects Linear Regression Models we show that earnings of employees with vocational education are higher in the initial phase of their career. However, generally educated catch up over the time on the labor market. Life-cycle differences in earnings are more pronounced in the United Kingdom than in the Netherlands and Germany." The analysis in this paper focuses on employees with upper-secondary educational level. Employees with either higher (i.e. tertiary) or lower education are not regarded. (Autorenreferat, BIBB-Doku)
Das Paper wurde auf folgenden Konferenzen präsentiert:
XIX Meeting of the Economics of Education Association, Zaragoza, Spain, 08th - 09th of July 2010
XXIV Annual Conference of the European Society for Population Economics (ESPE), Essen, 09th - 11th of June 2010
Keywords: Berufliche Qualifikation; Bildungsabschluss; Einkommen; Berufseinmündung; Berufserfahrung